MEMAHAMI GEERTZ MEMBACA ISLAM JAWA - Fajar Syarif (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2019)
The article aims to reread Geertz's understanding of Javanese Religion which is divided into three variants namely abangan, santri and priyayi. The focus of the discussion is to discuss how Clifford Geertz understands the Javanese Islamic community. The method used in this writing is descriptive analytic, that is by doing a description and analysis. The description and analysis in question is a way of describing Geertz's understanding of Javanese religion which is reflected in the understanding of abangan, santri and priyayi. The primary data source is the book Clifford Geerzt, entitled Agama Jawa: Abangan, Santri, Priyayi dalam Kebudayaan Jawa, published by Bamboo Communication in Jakarta in 2013. Secondary data sources are from books and journals that are in accordance with the subject matter. The approach to writing uses the Paul Ricoeur interpretation method. The findings of this paper are that Geertz in understanding Javanese religion (read: Islam) is inseparable from the context of the reality of society at that time, both in terms of politics, economics and culture.